Listeria monocytogenes meningitis after fludarabine treatment - Kisiel, Elżbieta; Lutwin, Ewa; Wątek, Marzena (Contemporary Oncology/Współczesna Onkologia, 2003)
The role of purine analogues in the treatment of lymphoproliferative disorders has been known for a long time although they have many side effects. The most significant ones are immunosuppressive effects including the decline in the number of CD4(+) lymphocytes. These effects increase the risk of infectious complications including such opportunistic infections as these caused by Pneumocystis carini, Toxoplasma gondi, Candida albicans, Cryptococcus neoformans and Listeria monocytogenes. Moreover, as a result of a prolonged immunosuppression, the risk of the infection remains increased many months after cessation of treatment. Immunosuppressed patients constitute about 50% of adult listeriosis cases. The most common presentations are acute and subacute meningitis, bacteremia and peritonitis are less common. Listeriosis is more common in patients pretreated with cytostatics or treated with corticosteroids and purine analogues at the same time. As a result of prolonged immunosuppression caused by purine analogues Listeria monocytogenes infection is still likely several months after treatment. A 67-year-old man with CLL treated with multiagent chemotherapy, and Fludarabine and Cyclophosphamide as a second-line therapy developed after two courses of chemotherapy rapidly progressing symptoms of meningitis with a loss of consciousness and tetraparesis. Spinal tap culture showed Listeria monocytogenes. CD4(+) count was within standard limits on the onset of infection and reached the nadir at the time of restoration to health. CD4(+) count is still below normal 18 months after cessation of Fludarabine treatment.